Improving Organizational Citizenship Behavior through Job Satisfaction, Leader-Member Exchange, and Work-Life Balance - Heriyadi Heriyadi; Heru Kurnianto Tjahjono; Meika Kurnia Puji Rahayu (Binus Business Review, 2020)
The research aimed to analyze the effect of leader-member exchange, work-life balance, and job satisfaction on Organizational Citizenship Behavior (OCB). The respondents were nursing staff at a hospital in Indonesia. The sample was 169 respondents, taken using a purposive sampling technique. Structural Equation Modeling (SEM) method was applied as the data analysis techniques with the application AMOS 22.0. Based on the results, the research finds that first, leader-member exchange and work-life balance have a positive and significant effect on job satisfaction and OCB. Second, job satisfaction affects OCB positively and significantly. Third, job satisfaction mediates the influence of leader-member exchange on OCB significantly. Fourth, job satisfaction also mediates the effect of work-life balance on OCB significantly. In conclusion, fostering OCB in hospitals is very important to produce better health service performance. The research shows that by increasing leader-member exchange, worklife balance, and job satisfaction, it can improve OCB. Overall, the research presents a significant contribution to the development of research in the field of human resource management and organizational behavior in the health sector in Indonesia.